How Learning Transfers. (March 2015) - Plack, Margaret M.; Goldman, Ellen F.; Wesner, Marilyn; Manikoth, Nisha; Haywood, Yolanda
<x xml:space="preserve">Abstract</x> Purpose Faculty development programs have been criticized for their limited assessment methods, focused only on the learners and limited to satisfaction measures or self-reported behavior changes. Assessment of organizational impact is lacking. This study explored the impact of faculty education fellowship graduates on their organization and how that impact occurred. Method The design was a qualitative study of 13 departments across three institutions, partnered with the George Washington University School of Medicine and Health Sciences. In-depth interviews with 13 supervisors and 25 peers of graduates were conducted in fall 2012 to examine graduates' organizational impact related to program purposes: enhancing teaching skills, pursuing scholarship in education, and developing leadership potential. Triangulation, purposive sampling, rich descriptions, and member checks minimized bias and optimized transferability. Results A model of how graduates of a faculty education fellowship transfer learning to peers and their organizations emerged. Analysis of interview responses showed that in the presence of environmental facilitators, graduates exhibited enhanced confidence and five new behaviors. Graduates raised peer awareness, leading to changes in individual and group practices and development of shared peer understanding. Analysis suggests they facilitated a culture of continuous learning around teaching, scholarship, and leadership. Conclusions This study enhances traditional assessment of faculty education fellowship programs by examining the impact that graduates had on peers and work groups. A model is proposed for how graduates interact with and impact work group processes and practices. This model can facilitate more comprehensive program assessments, which can demonstrate program impact beyond the individual participant.